POLA ASUH ORANG TUA DENGAN KEBERHASILAN TOILET TRAINING PADA ANAK - Lintang Asri Lunari (Yayasan Nusantara Hasana Berdikari, 2023)
Toilet training is one of the developmental tasks that must be passed by children, to form independence, discipline and sensitivity in children. toilet training process. Objective of this study to find out the relationship between parenting style and the success of toilet training. This research went through the process of searching articles and journals from Google Scholar, ISJD, Pubmed, Proquest, Spinger with keywords and inclusion criteria in the journal period 2017-2021. After the screening process, 17 related journals were obtained and filtered into 13 synthesis matrix results grouped into 3 categories, namely input, process, output to be discussed. There are 10 discussions about parenting, 7 discussing toilet training. Democratic parenting can help in the success of toilet training, democratic parenting gives freedom to children but still with direction and guidance, because democratic parenting more respects the rights of children so that children feel comfortable and loved.